2014
DOI: 10.1371/journal.pone.0094127
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Blockers Inhibit Adipocyte Differentiation and Fat Mass Accumulation

Abstract: Geldanamycin derivatives are benzoquinone ansamycin antibiotics that bind to Hsp90 and alter its function. The alteration of Hsp90 activity limits some cellular hormonal responses by inhibiting nuclear receptors activation. The nuclear receptors activity, such as PPARγ, the mineralocorticoid and glucocorticoid receptors (MR and GR) play a critical role in the conversion of preadipocytes to mature adipocytes. Given the importance of these nuclear receptors for adipogenesis, we investigated the effects of geldan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Modulation of MR activity can occur through posttranslational modification by protein kinases and enzymes involved in adipogenic pathways (Faresse 2014). Among the transcription factors involved in adipogenesis, a relevant role for CREB has been demonstrated.…”
Section: Modulation Of Mr Activity By Adipogenic Signaling Pathways Amentioning
confidence: 99%
See 1 more Smart Citation
“…Modulation of MR activity can occur through posttranslational modification by protein kinases and enzymes involved in adipogenic pathways (Faresse 2014). Among the transcription factors involved in adipogenesis, a relevant role for CREB has been demonstrated.…”
Section: Modulation Of Mr Activity By Adipogenic Signaling Pathways Amentioning
confidence: 99%
“…However, phosphorylation of MR has been detected in renal cells, cardiomyocytes and adipocytes (Galigniana 1998, Desarzens et al 2014. Aldosterone itself is able to induce phosphorylation of MR on serine residues located in the N-terminal domain with subsequent proteosomal degradation of the receptor (Faresse et al 2012).…”
Section: Modulation Of Mr Activity By Adipogenic Signaling Pathways Amentioning
confidence: 99%
“…Nguyen et al ( 25 ) have shown that Hsp90 chaperones Ppar ␥ , while Desarzens et al ( 32 ) have shown that Hsp90 inhibition blocks adipocyte lipid accumulation in vivo. Indeed, Hsp90 interacts with and chaperones many different transcription factors ( 33 ), most notably the nuclear hormone receptors, providing precedent for this observation ( 34 ).…”
Section: Y344h/y344hmentioning
confidence: 99%
“…We previously found that pharmacological inhibition of both MR and GR abolished the adipogenesis and prevented adipose tissue expansion and adipocyte hypertrophy during a chronic high fat diet (Desarzens et al 2014). Other studies evidenced that GR has a more prevalent role, compared with MR, in promoting the maturation of preadipocytes (Lee & Fried 2014a).…”
Section: Introductionmentioning
confidence: 97%